The Challenge and Opportunity for MOOCs for Teaching Writing - Bloch, Joel (Journal of Academic Writing, 2016)
Massive Open Online Courses (MOOCs) have been touted as alternative approaches to face-to-face teaching and the design of learning spaces. MOOCs allow teachers to rearrange traditional classroom activities and use technologies sometimes in new and different ways to provide new ways of teaching. Recently, they have been implemented for the teaching of writing to provide greater access to these courses. I examine the possibilities and challenges of using these technologically-enhanced spaces for teaching composition. I first discuss the differences in the designs of MOOCs and how these approaches were applied to teaching writing. Based on my own participation in composition MOOCs as well as a variety of other MOOCs since 2008, I introduce three composition MOOCs, which although designed as L1 courses, involved thousands of participants with varying backgrounds from all over the world. I discuss how these MOOCs responded to challenges and how the participants could negotiate their own learning, such as by choosing which assignments they wanted to complete or determining how much peer review they wanted. I conclude that these courses demonstrate how MOOCs have created new learning spaces that can influence face-to-face approaches to teaching writing.